2014
DOI: 10.1177/0192623314546559
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Soluble Guanylate Cyclase Agonists to Rats Results in Osteoclastic Bone Resorption and Remodeling with New Bone Formation in the Appendicular and Axial Skeleton

Abstract: Orally administered small molecule agonists of soluble guanylate cyclase (sGC) induced increased numbers of osteoclasts, multifocal bone resorption, increased porosity, and new bone formation in the appendicular and axial skeleton of Sprague-Dawley rats. Similar histopathological bone changes were observed in both young (7-to 9-week-old) and aged (42-to 46-week-old) rats when dosed by oral gavage with 3 different heme-dependent sGC agonist (sGCa) compounds or 1 structurally distinct heme-independent sGCa compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The NO-sGC-cGMP pathway is also an important regulator of the metabolism and function of osteoblasts and osteoclasts and regulates bone formation, resorption and remodeling [ 64 , 65 ]. Although, the initial animal studies of riociguat activity in adolescent rats and mice showed various degrees of bone resorption and remodeling in the femur and tibia [ 17 ], clinical studies in adults did not show any adverse effect on bones. In addition, we have reported normal bone densities in mice lacking GC1 demonstrating that GC1 does not play an important role in specifying bone density [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NO-sGC-cGMP pathway is also an important regulator of the metabolism and function of osteoblasts and osteoclasts and regulates bone formation, resorption and remodeling [ 64 , 65 ]. Although, the initial animal studies of riociguat activity in adolescent rats and mice showed various degrees of bone resorption and remodeling in the femur and tibia [ 17 ], clinical studies in adults did not show any adverse effect on bones. In addition, we have reported normal bone densities in mice lacking GC1 demonstrating that GC1 does not play an important role in specifying bone density [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, the FDA has raised a concern for a future reference for use of riociguat in pediatric patients, even when conducting clinical trials [ 67 ]. However, Homer et al, in their recent study using 7 to 9 weeks old Sprague Dawley rats, demonstrated that while riociguat initially caused adverse bone changes, they found these bone changes reversible, with partial recovery after 2 weeks and no bony changes at all after 5 weeks of recovery [ 17 ]. Similarly, in our study, we found that daily IP injection of riociguat for 9 days did not affect trabeculae, bone length and bone volume in secondary spongiosa of femur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented through internal and published studies that high concentrations of sGCa cause DIVI in the mesenteric arteries of rats. 28 Thus, we used a proprietary sGCa that in internal studies caused highly reproducible vascular injury in the mesenteric arteries, in the optical imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented through internal and published studies that high concentrations of sGCas cause DIVI in the mesenteric arteries of rats. 28 The optical agents were used to quantitatively measure DIVI in rat mesenteric arteries after oral dosing of the sGCa, and concordance was assessed with histopathology and immunohistochemistry.…”
Section: -25mentioning
confidence: 99%